2015
DOI: 10.1016/j.aogh.2015.08.005
|View full text |Cite
|
Sign up to set email alerts
|

Climate Change and Water Scarcity: The Case of Saudi Arabia

Abstract: International, multidisciplinary cooperation and collaboration will be needed to promote global water security and to protect human health, particularly in low-income countries that do not have the resources necessary to adapt on their own.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
111
0
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 237 publications
(158 citation statements)
references
References 24 publications
1
111
0
3
Order By: Relevance
“…The Global Water Partnership (2000) and Al Saidi (2017) have pointed out that water scarcity in most global communities requires that their security be treated as a main topical issue within sustainable development at large. It is, however, observed that obstacles such as rising climate vulnerabilities exacerbate water scarcity (Natural Resource Defence Council, 2010;Ziervogel et al, 2014;DeNicola et al, 2015;Nhamo et al, 2018), thus raising profound concerns as to how a sustainable supply of critical resources can be attained. This underlines the persistent necessity for society globally to strive for a balanced system across the management of natural resources.…”
Section: Introductionmentioning
confidence: 99%
“…The Global Water Partnership (2000) and Al Saidi (2017) have pointed out that water scarcity in most global communities requires that their security be treated as a main topical issue within sustainable development at large. It is, however, observed that obstacles such as rising climate vulnerabilities exacerbate water scarcity (Natural Resource Defence Council, 2010;Ziervogel et al, 2014;DeNicola et al, 2015;Nhamo et al, 2018), thus raising profound concerns as to how a sustainable supply of critical resources can be attained. This underlines the persistent necessity for society globally to strive for a balanced system across the management of natural resources.…”
Section: Introductionmentioning
confidence: 99%
“…The Intergovernmental Panel on Climate Change (IPCC) has explained the vulnerability of climate change in terms of exposure to hazards and the capacity to adapt. Understanding the interaction of climatic parameters and environment is likely to reduce vulnerability, such as growing new crops suitable to climate change and efficient management of water resources [13,14]. Increase in temperature might decrease dissolved oxygen (DO) and increase dissolved organic matter (DOM) and salinity in source water [2,15].…”
Section: Introductionmentioning
confidence: 99%
“…The increased water requirements of growing populations, and their agricultural and industrial needs, are compounded by shrinking of temperate regions and subsequent expansion of hot arid zones around the world, exacerbating issues of water insecurity in developing nations (Intergovernmental Panel on Climate Change [IPCC], ; Stringer et al, ). Though much work has focused on understanding the complex relationships between water demand and supply, without adequate understanding of variation in water turnover and water requirements across populations living in different environments, large number of people may continue to face a growing risk of water insecurity (DeNicola, Aburizaiza, Siddique, Khwaja, & Carpenter, ; Organization for Economic Co‐operation and Development, ; UNESCO, ).…”
Section: Climate Changementioning
confidence: 99%